Newborn Screening in Japan - Tajima, Toshihiro; Yamaguchi, Seiji (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
"Newborn Screening in Japan-2021" is a topical collection of the International Journal of Neonatal Screening. Japan's newborn mass screening (NBS) was started in 1977 at the national level as a national project. Subsequently, screening was conducted for six diseases. From 2014 a tandem mass analyzer (tandem mass) was introduced nationwide, and in addition to the conventional amino acid metabolism disorders urea cycle disorders, organic acid metabolism disorders and fatty acid metabolism disorders have joined the target diseases. Screening is currently conducted for 20 diseases. The acceptance rate of mass screening in Japan is 100%, and top-level screening measures available in the world, such as a quality control system and an inspection system, are carried out. This book is an overview of the history, current status and future of NBS in Japan. I hope that readers are interested in this book.